Spectroscopic Studies of a New Mixed Ligand Complex of Fe(III) in Aqueous Medium - Aziz, B.K. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
A spectrophotometric study of Fe(III) mixed ligand complex has beenperformed  involving  1,4 phenylenediamine  (A) and  anthran i lic acid (B) ligand  at 25Â°C  and  aconstant  ionic strength  of  Âµ= 0.05M  NaC I04â€¢  The optimum  pH was  found  to be pH=4.l. The format ion  rat io of the new complex   is   determined   to   be   2:1:4  of   Fe(III):(A):(B).   The   molar absorptivity was determined to be :::::: 0.5 x  I 04â€¢  Stepwise spectrum change of the complex formation  is recorded by continuous flow system. Keywords: Mixed ligand complex, Fe(III)